Analisis Kelayakan Modul Model Project Based Learning Berbasis Kearifan Lokal Dalam Upaya Meningkatkan Pemahaman Konsep Fisika Materi Suhu Dan Kalor - Melani Dyah Ayu Sukma; Tsania Nur Diyana (Program Studi Pendidikan Fisika Universitas Katolik Widya Mandira, 2024)
This development research aims to determine the feasibility of learning tools in the form of learning modules with a project based learning model to increase students' conceptual understanding of temperature and heat material. This research is based on the results of preliminary research which states that students still have a low understanding of concepts in the material and lack the latest innovations in learning tools. This research was carried out using the 4D model, but in this research This is only done until the development stage. The learning tools developed in this research are learning modules. The feasibility of the learning module was reviewed based on the validation results carried out by 4 expert validators, with the results of the analysis all producing scores in the very good category for all aspects of the learning module. Based on the results of the validator analysis, it can be concluded that in this research the learning module with the project based learning model developed by the researcher is suitable for use to increase students' understanding of physics concepts in temperature and heat material.